Thermodynamic Modeling of Chiral Compounds Solubility Using Correlative and Predictive Models - Salimi, Morteza; Zarenezhad, Bahman; Fakhraian, Hossein; Choobdari, Ebrahim (Journal of Applied Solution Chemistry and Modeling, 2015)
Many intermolecular forces and parameters affect the solubility of a compound in a solvent. Various thermodynamic models are presented to predict these parameters and determine solid liquid equilibrium data. By selecting suitable thermodynamic model for solubility modeling, calculation error is reduced and the results will be closer to the experimental data. Herein, the ability of two predictive and two correlative models in solubility modeling of chiral compounds is investigated. Thus, solubility of pure and racemic forms of chiral Ketamine, Mandelic acid and 3-Chloromandelic acid is evaluated using UNIQUAC and NRTL models. The solubility modeling of pure and racemic forms of Ketamine in Ethanol is also determined by UNIFAC and NRTL-SAC models. There are good agreement between experimental data and results of NRTL and UNIQUAC models. Predictive NRTL-SAC model shows smaller deviation than UNIFAC in solubility determination of pure and racemic form of Ketamine.